Herbal Medicine and Women's Mental Health - L Kashani; S Akhondzadeh (Institue of Medicinal Plants, ACECR, 2009)
Herbal medicine is being increasingly used by women to prevent diseases, promote health and treat different diseases including a number of psychiatric disorders. The use of herbal drugs is increasing in the western world. The use of herbal drugs during pregnancy has been studied to various extents in different countries. However, more information is required regarding the impact of herbal medicine on conventional treatment, because such information can have important for public health and mental health care. This review focuses on herbal medicine and mental health of women in particular premenstrual syndrome and maternal depression.